KONTRIBUSI E-WOM TERHADAP PERILAKU KONSUMTIF - Yustati, Herlina (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2018)
This article starts from Laila Hifziati's research stating that in addition to being the most up-to-date promotional tool, eWOM culinary on Instagram has formed a consumptive culture. Starting from this study, this study aims to determine how much eWOM contributes through the shopee platform (Shopee platform dominates mobile applications and ranks first as the most popular shopping application on the Android and IOS platforms) on the consumptive behavior of Bengkulu IAIN students. Before knowing the size of the contribution, the results of the study show that e-Wom has a positive effect on consumptive behavior, that is, the more frequent e-Wom is used in Shopee applications, the more consumptive behavior will be. While the amount of e-Wom's contribution to consumptive behavior is 42.7%, while 57.3% is influenced by other factors